2004
DOI: 10.1111/j.0953-816x.2004.03190.x
|View full text |Cite
|
Sign up to set email alerts
|

GAP‐43 overexpression in adult mouse Purkinje cells overrides myelin‐derived inhibition of neurite growth

Abstract: Up-regulation of growth-associated proteins in adult neurons promotes axon regeneration and neuritic elongation onto nonpermissive substrates. To investigate the interaction between these molecules and myelin-related inhibitory factors, we examined transgenic mice in which overexpression of the growth-associated protein GAP-43 is driven by the Purkinje cell-specific promoter L7. Contrary to their wild-type counterparts, which have extremely poor regenerative capabilities, axotomized transgenic Purkinje cells e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 56 publications
(116 reference statements)
2
39
1
1
Order By: Relevance
“…In both experimental groups, there were no clear differences from previous descriptions about myelination of Purkinje axons (Gianola et al, 2003;Gianola and Rossi, 2004;Clark et al, 2005). In control material (Fig.…”
Section: Effects Of Cspgs Degradation On Axon Myelinationcontrasting
confidence: 48%
See 2 more Smart Citations
“…In both experimental groups, there were no clear differences from previous descriptions about myelination of Purkinje axons (Gianola et al, 2003;Gianola and Rossi, 2004;Clark et al, 2005). In control material (Fig.…”
Section: Effects Of Cspgs Degradation On Axon Myelinationcontrasting
confidence: 48%
“…Injection of anti-Nogo-A antibodies in the cerebellar cortex induces sprouting from Purkinje axons in the granular layer (Buffo et al, 2000), and a similar phenomenon is observed after injury in GAP-43 (growthassociated protein-43)-overexpressing Purkinje cells (Buffo et al, 1997;Gianola and Rossi, 2004). In both conditions, in addition to the outgrowth of terminal fibers from the infraganglionic plexus, sprouting also occurs along the corticofugal neurite, and this phenomenon may be accompanied by disruption of the normal axon-myelin relationship (Gianola and Rossi, 2004).…”
Section: Effects Of Cspgs Degradation On Axon Myelinationmentioning
confidence: 81%
See 1 more Smart Citation
“…[7][8][9][10][11] GAP-43 contributes to axon sprouting and regeneration in the peripheral nervous system, in the optic nerve, in the Purkinje cells of the cerebellum, in mossy fibers of the hippocampus and in the raphe-spinal descending spinal tracts. [12][13][14][15] However, GAP-43 alone does not significantly promote axon regeneration of the corticospinal tracts and the dorsal root ganglia ascending spinal fibers, but does so after dorsal column lesions when overexpressed together with CAP-23. 16 Thus far, it has been shown that GAP-43 is regulated at both the transcriptional and post-transcriptional levels.…”
mentioning
confidence: 97%
“…Overexpression of major growth cone proteins, such as GAP-43 or CAP-23, in transgenic mice induces spontaneous sprouting in different populations of PNS and CNS neurons, and promotes collateral reinnervation at the neuromuscular junction (Aigner et al, 1995;Caroni et al, 1997). When the GAP-43 gene is specifically targeted to Purkinje cells, which are peculiar for their poor regenerative potential (Rossi et al, 1995;Dusart et al, 1997;Carulli et al, 2004), injured axons vigorously sprout into the growthinhibitory white matter environment (Buffo et al, 1997;Gianola and Rossi, 2004). Sprouting, but not regeneration, has been also reported for GAP-43 overexpressing thalamic neurons (Mason et al, 2000), indicating that up-regulation of individual genes may enhance axon plasticity, but it is not sufficient to sustain long-distance neuritic elongation.…”
Section: Overexpression Of Neuronal Growth Genesmentioning
confidence: 99%